Studi Komparatif Mengenai Mindset antara Pria/Wanita yang Terikat Pernikahan dan Pria/Wanita yang Bercerai di Kota Bandung - Thomas, Maria Carmelita Patricia; Maria, Cindy (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2021)
This research was conducted to determine the differences about mindset between married man/woman and divorced man/woman in Bandung. Respondents in this study are man/woman who are married to only one person and man/woman who are divorced and have not remarried and are domiciled in Bandung. The sample in this study amounted to 100 people, 50 people who were married and 50 people who were divorced. The sampling technique used was snow ball sampling. Measurements were conducted with Mindset in Relationship measuring instrument which consists of 27 items. This measuring instrument has a validity range of 0,38 – 0,73 and reliability of 0,91. This study used the independent t-test technique to see the differences between mindset of married man/woman and divorced man/woman in Bandung. The results showed that there was a difference in the mindset between married man/woman and divorced man/woman in Bandung. The conclusion of this research is that married man/woman in Bandung have mindset that tends to be more growth, while divorced man/woman in Bandung have a more fixed mindset.